Enhancing Christian religious education through self-regulated learning strategies: A pre-experimental study at Kadesi Theological school - Suparti, Hana; Wahyuni, Sri (Indonesian Research Journal in Education |IRJE|, 2026)
This research aims to examine the effectiveness of Self-Regulated Learning (SRL)-based learning in improving students' speaking skills in Christian communication and homiletics courses at Kadesi Theological College. The study used a pre-experimental design with a one-group pre-test and post-test, involving 24 fifth-semester students in the Christian Religious Education Study Program. Data were collected through speaking ability assessments, classroom observations, reflection journals, and learning evaluations. The results showed a significant increase in pronunciation, intonation, fluency, and the ability to organize theological ideas after the implementation of the SRL strategy. The students' average score increased from 67.88 in the pre-test to 81.08 in the post-test. In addition, students showed increased self-confidence, active participation, and independence in the learning process. This research indicates that SRL-based learning can support reflective learning and improve theological communication competency in the context of Christian religious education.